ARTE Y ESPIRITUALIDAD: LA PRESENCIA DE GOETHE EN LA PINTURA DE KANDINSKY - Cicero Cunha Bezerra (Travessias, 2011)
W. Kandinsky (1866-1944) is, with no doubt, one of the most brillant artists of universal painting. Creator of the so-called suprematism, he inaugurated a new style of painting and its content. Marked by theoretical influences that remember directly Rudolf Steines Theosophy and goethian (1749-1832) Neoplatonism, his works turn themselves a privileged source for those who are interested in the dialogue between Philosophy and abstract modern Art. In this research, I will try to identify Neoplatonic elements that are present in Kandinskys theoretical texts Spiritual in Art and On the problem of form, theoretical texts that have their direct origin from the influence of Goethes Colors Doctrine